Expansion of southern distributional range of Ucides occidentalis (Decapoda: Ucididae) and Cardisoma crassum (Decapoda: Gecarcinidae) - Alemán, Solange (2017)
Is recorded the species of crabs brachyuran Ucides occidentalis (mangrove crab) and Cardisoma crassum (Blue crab or without mouth) in the mangroves of San Pedro (Piura), expanding its geographical distribution south of Tumbes, which was the known limit. The habitat of these species is characterized by the presence of two varieties of mangrove trees, Jeli white (Laguncularia racemosa) and salty Jeli (Avicenia germinans) and halophytic shrub called glass (Batis maritima), it observing that the depth of the burrows is shallow (< 60 cm). Biometric information and some biological aspects of the collected specimens are also presented.